Home Isolated COVID-19 patients adhering to recommended guidelines: a cross sectional survey in Karachi - Luxmi, Shobha; Munazza Obaid; Sadaf Zia; Fatiam Zulfiqar Siddiqui; Musfirah Danyal Barry; Saba Zaheer; Faiza Zakaria (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess compliance level of coronavirus disease-2019 patients with recommended isolation guidelines. Methods: The cross-sectional phone-based survey was conducted in Karachi, from March to October 2020 after approval from the ethics review board of Dow University of Health Sciences, Karachi, and comprised patients of either gender who had been tested positive and were advised home isolation due to mild/asymptomatic nature of their infection. Data was collected using a predesigned 42-item questionnaire in the light of the guidelines issued by the National Institutes of Health, Islamabad, Pakistan. Data was analysed using SPSS 20. Results: Of the 450 patients approached, 305(68%) responded; 176(57.7%) females and 129(41.1%) males. The overall mean age was 35.16+/-14.15 years (range: 13-78 years). Of the total, 9(2.95%) patients did not isolate themselves at all, 51(16.7%) came into contact with other people, 75(24.6%) broke the home isolation and 69(22.6%) were sharing their rooms with other family members. Overall, 260(85.2%) participants were keeping themselves updated with the changes in the guidelines through conventional and social media. Conclusion: Coronavirus disease-2019 patients who were advised home isolation adhered to some but not all of the recommendations. Key Words: COVID-19, Home isolation, Protective measures, Home management, SARS-CoV-2.